The Partnership Benefits in Low-cost Apartment Implementation Program in Surabaya Metropolitan Area - M. Muntoha; Ria A.A. Soemitro; Farida Rachmawati (IPTEK Journal of Proceedings Series, 2015)
The low-cost apartment implementation program is one of the reliable solutions to reduce housing needs in East Java Province. Eventhough there were many problems facing the low cost apartmen program implementation, private sector is still highly expected to contribute in this program. The objective of this research is to identify public private partnership benefits from stakeholder perception. The benefit variables to better understand the low-cost apartment implementation which obtained from literature review studies were then validated by 32 purposive sampling respondents from both government and private sectors. These variables were then identified and analyzed using statistical analysis. The results show that the benefit factors from both government and private sector perception are better risk allocation and accelarate infrastructure development